User Experience Design for Information Technology Career Preparation Platform Using the Design Thinking Method - Tri Ananta, Mahardeka; Fanani, Lutfi; Adista Sihombing, Ivanna; Abidin, Zainul (Journal of Information Technology and Computer Science, 2023)
Digital talent is crucial in the thriving Information Technology (IT) industry. Hence, numerous countries seek digital skills to stay competitive in the current era. In Indonesia, the challenge lies not in quantity but in the readiness of digital talents to enter the professional world. To address this issue, we observed the IT career readiness of fresh graduates and senior students from the Faculty of Computer Science, Universitas Brawijaya. The observation revealed that 82.9% of 70 respondents stated doubts about their career preparations in the IT domain. These doubts stemmed from perceived inadequacy in technical skills, lack of readiness in developing a curriculum vitae and facing job interviews. Given the need for career preparation in the IT domain, we address the development of a platform to assist aspiring IT talents. This study proposes a solution as an IT career preparation application designed using the Design Thinking method The proposed design was tested using the Usability Evaluation, yielding an effectiveness rate of 100% and an efficiency value of 0.08 goals/sec. Furthermore, a satisfaction test was conducted using the SUS questionnaire, resulting in a score of 94.75 (excellent).